2004
DOI: 10.1097/01.sla.0000140752.74893.24
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Hospital Volume and Outcome in Bariatric Surgery at Academic Medical Centers

Abstract: Bariatric surgery performed at hospitals with more than 100 cases annually is associated with a shorter length of stay, lower morbidity and mortality, and decreased costs. This volume-outcome relationship is even more pronounced for a subset of patients older than 55 years, for whom in-hospital mortality was 3-fold higher at low-volume compared with high-volume hospitals. High-volume hospitals also have a lower rate of overall postoperative and medical care complications, which may be related in part to formal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
201
1
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 371 publications
(219 citation statements)
references
References 12 publications
9
201
1
8
Order By: Relevance
“…There is an association between increased hospital volumes with improved outcomes in a number of complex, high-risk operations [20,22,25]. The current study similarly identified a relationship between incremental annual increase of 10 case with improved outcomes.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…There is an association between increased hospital volumes with improved outcomes in a number of complex, high-risk operations [20,22,25]. The current study similarly identified a relationship between incremental annual increase of 10 case with improved outcomes.…”
Section: Discussionsupporting
confidence: 65%
“…One of the first studies examining the relationship between hospital volume and surgical outcomes was published in 1979 by Luft et al [14]. Since that time, there have been numerous studies published on the association between hospital volume and surgical outcomes for complex, high-risk operations [15][16][17][18][19][20][21]. The overwhelming majority of these studies have demonstrated that high-volume hospitals have improved outcomes, particularly for high-risk operations.…”
Section: Introductionmentioning
confidence: 99%
“…This method of risk assessment has been verified and validated by the Agency for Healthcare Research and Quality (AHRQ) [33]. Severity of illness accounts for a number of patient variables and weights them in the context of patient illness, including other co-morbid conditions, age and diagnoses [34][35][36][37][38][39][40][41].…”
Section: Methodsmentioning
confidence: 99%
“…However, a recent study using that database identified fewer than one-half as many patients as this study (n = 688) and had no means of identifying use of HBOT as an adjunct to surgical debridement [72,73]. The UHC's risk-stratification method has been validated by the AHRQ and has been used by a number of other researchers to adjust outcomes after various interventions [34][35][36][37][38][39][40][41]72]. Therefore, despite the possible limitations of our severity of illness measure, given the database's power to yield a relatively large cohort for a rare disease, and an ever-rarer intervention, we believe that our analysis is meaningful for clinicians considering whether or not to use HBOT to treat NSTI.…”
mentioning
confidence: 99%
“…The 30‐day operation mortality was reported to be 2% in 2004 and decreased to 0.2% in 2009 through the high‐quality bariatric center program in the USA 19, 20. Well‐experienced surgeons, fully trained in laparoscopic techniques and proctorship, teamwork and agdequate volume are important for a high‐quality bariatric surgical center 21. Improvements in technology, operative techniques, results of clinical trials and accumulation of experience all contributed to this progress 22.…”
Section: Increase In Numbers and Better Safetymentioning
confidence: 99%